KINETICS STUDY OF MERCAPTOETHYL OLEATE SYNTHESIS - Tresnika Az Zahrany, Deanthy
Mercaptoethyl oleate (MEO) is one of the mercaptoethyl ester compounds of fatty acids (MEAL) which can be used as raw material for the production of organotin compounds in polyvinyl chloride (PVC) thermal stabilizers. MEO is synthesized through the esterification of oleic acid with mercaptoethanol using a strong acid catalyst, such as pTSA (para-toluene sulfonic acid). However, there may be side reaction that occurs as a result of the presence of 2 reactive functional groups on mercaptoethanol. This results in the formation of a thioester compound which has the potential to reduce the concentration of sulfhydryl in MEO products. This study aims to analyse the kinetic reaction of MEO synthesis from oleic acid esterification with pTSA catalyst. In addition, this study also researched the effect of variations in reaction time, temperature, initial reactant ratio, and catalyst ratio towards the kinectic reaction of MEO synthesis. The parameters of kinetic reaction researched in this study include, reaction rate constant, pre-exponential factor, and activation energy. The acquisition of primary data of acid value and SH value in various conditions has been carried out by Wang et al. (2012). The data is used in modeling simulations using MATLAB software. The modeling used is a unidirectional reaction in which each reactant affects the reaction as the first order. According to the findings in the literature, maximum oleic acid conversion and MEO yield was reached at a reaction time of 3.5 hours, temperature of 75?, and catalyst ratio of 1%-mass. Modeling simulation with first order reaction assumption shows that the reaction rate constant for the formation of MEO at optimum reaction time is 0,5054 M- 1.h-1, at optimum temperature is 1,116 M-1.h-1, and at optimum catalyst ratio is 0,9958 M- 1.h-1. On the other hand, an increase in the reactant ratio from 0,9 mol/mol to 1,23 mol/mol is followed by an increase in the reaction rate constant from 0,13 M-1?h-1 to 1,86 M-1?h-1. MEO synthesis follows the Arrhenius equation with an activation energy of 66,57 kJ/mol and a pre-exponential factor value of 6,85 × 109 M-1.h-1.